Conference 2012 Keynote Address: Sa Society for History Teaching annual congress (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
“The separation of societies from their past: An under-appreciated tragedy” South Africa’s population consists of several groups of peoples, roughly (linguistically) defined by the number of languages used in schools. Each of these groups has a past of its own, and many occupy land where generations of ancestors are buried. They have their own origins, kinships and customs. Government acknowledges (admits) the diversity of cultures and provided among others Heritage Day to commemorate and celebrate not only the separate but also the shared histories. Unfortunately its good intentions went up in the smoke of “Braai Dag”. Neither do the CAPS History syllabi support the government’s aims in this respect. I regard them as generally narrow and politically correct in outlook, because they ignore much of what is important to the remainder. A great need for people educated and trained in local and regional history exists across the country, which not only affects government’s Conservation Management and Education System but almost all walks of life, and dangerously so in politics and parliament. Chairman, Ladies and Gentlemen.
Keywords: separation; languages; shared histories; heritage; customs; schools; diversity of cultures; local and regional history